ESPEN guideline on hospital nutrition. Issue 12 (December 2021) - Thibault, Ronan; Abbasoglu, Osman; Ioannou, Elina; Meija, Laila; Ottens-Oussoren, Karen; Pichard, Claude; Rothenberg, Elisabet; Rubin, Diana; Siljamäki-Ojansuu, Ulla; Vaillant, Marie-France; Bischoff, Stephan C.
Summary: In hospitals through Europe and worldwide, the practices regarding hospital diets are very heterogeneous. Hospital diets are rarely prescribed by physicians, and sometimes the choices of diets are based on arbitrary reasons. Often prescriptions are made independently from the evaluation of nutritional status, and without taking into account the nutritional status. Therapeutic diets (low salt, gluten-free, texture and consistency modified, …) are associated with decreased energy delivery (i.e. underfeeding) and increased risk of malnutrition. The European Society for Clinical Nutrition and Metabolism (ESPEN) proposes here evidence-based recommendations regarding the organization of food catering, the prescriptions and indications of diets, as well as monitoring of food intake at hospital, rehabilitation center, and nursing home, all of these by taking into account the patient perspectives. We propose a systematic approach to adapt the hospital food to the nutritional status and potential food allergy or intolerances. Particular conditions such as patients with dysphagia, older patients, gastrointestinal diseases, abdominal surgery, diabetes, and obesity, are discussed to guide the practitioner toward the best evidence based therapy. The terminology of the different useful diets is defined. The general objectives are to increase the awareness of physicians, dietitians, nurses, kitchen managers, and stakeholders towards the pivotal role of hospital food in hospital care, to contribute to patient safety within nutritional care, to improve coverage of nutritional needs by hospital food, and reduce the risk of malnutrition and its related complications.